(untitled) (Al-Academy, 2020)
The current research discusses the topic of the formal data within the methodological framework through defining the research problem, limits and objectives and defining the most important terms mentioned in this research. The theoretical framework in the first section addressed (the concept of the Bauhaus school, the philosophy of the Bauhaus school and the logical bases of this school). The second section dealt with (the most important elements and structural bases of the Bauhaus school) which are considered the most important formal data of this school and their implications on the fabrics and costumes design. The research came up with the most important indicators resulting from the theoretical framework.Chapter three defined the research method, community, and sample and analysis of the model. Chapter four stated the results and the most important of which are:1- The sample is representative of the most important formal data of the Bauhaus school its implications of thee fabrics and female costumes designs. 2- Design elements represent a major and distinguished role for all the models of the sample thus achieving the aesthetic function.3- The formal implications of the Bauhaus school in the fabrics and costumes designs came as a result of employing these data in all the models of the sample. 4- The use of the vocabulary and the formal elements of the Bauhaus was an expression of the civilizational and cultural content specific to this school